A Case Report on Sutika Janya Shrirashoola with special reference to Migraine (International Journal of Ayurveda and Pharma Research, 2023)
In all Samhita different chapter is devoted to Shiro-Roga and detailed explanation about causes, clinical symptoms and treatment are discussed. In Shiro-Roga, Shirashoola is the main symptoms. In India, headache is the most common problem and found in maximum females. Causes can be anything from wrong diet, digestive problem, or stress of daily life. In present case, a 28 years female suffering from severe headache since last five years whose all diagnostic reports were normal. She had taken allopathic treatment for past five years but did not get significant relief. After taking detailed history, it was concluded that the headache was due to improper follow up of Sutika paricharya. Abhayanga-swedan, Nasya and Shirodhara along with oral medication was prescribed for 15 days. Patient gets relief in headache as well as associated symptoms within four days. Treatment was continued for two months and no reoccurrence was held after follow up also.